Understanding giant cell sarcoma of the head and neck: A population‐based study. Issue 9 (14th June 2021) - Sawhney, Rohan; Ahsanuddin, Salma; Sheorey, Lena; Wassef, David W.; Baredes, Soly; Park, Richard Chan Woo
Abstract: Background: Giant cell sarcomas (GCS) are rare head and neck neoplasms. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was analyzed for all patients who have been diagnosed with GCS from 1973 to 2014. Results: Four hundred and forty cases of GCS of the head and neck were identified. The average age at diagnosis was 74.4 years, 86.8% were white, 82.5% were male, 70.7% were insured, and 88.2% lived in an urban metropolitan region. Connective tissue was the most frequent primary site (42.5%). The 5Y‐DSS rate was 91.1%, while the 5Y‐OS was 54.6% for all cases. Patients treated with surgery alone had the highest 5Y‐DSS rate of 94.5. T‐classification odds ratio was a significant predictor of survival accounting for confounding variables on multivariate analysis. Conclusions: GCS presents most frequently in connective tissue of the head and neck with overall high probability of survival. The treatment of choice is surgery alone.